Hierarchic Visual Spatial Task Performance: Aspatial versus Spatial Majors. - Lloyd, Casandra; Lim, Randy (My University, 2009)
Navon (1977) developed a hierarchic visual spatial task in which stimuli were large letters, at the global level, made up of small letters, at the local level. Processing speed increases with practice at both the global and local levels. We hypothesize, therefore, that undergraduate students majoring in spatial majors, such as Art and Physics, would perform better at a hierarchic visual spatial task thatn would those in an aspatial major, such as psychology.
Color poster with text and tables.
Keywords: Visual perception--Testing; Visual perception--Psychological aspects; Performance--Psychological aspects; Posters